O telespectador presumido em De Frente com Gabi & Sem Censura - Silvia Lopes do Amaral (2014)
This study aims at investigating how the television shows De Frente com Gabi (SBT) and Sem Censura (Rede Brasil de Televisão) configure a presumptive TV viewer woven in their textual space. To accomplish this objective, it´s essential to understand how this contact is built up and which mechanisms are developed by media events. It so happens because in our point of view, tv programs are texts that establish a recipient, a requiring party for the communication process and for its significance. Therefore, based on the characteristics and strategies television shows have been producing and displaying in the last few decades in Brazil, mainly when studies regarding this issue are related to social interactive processes we focus on those two Brazilian TV, which have hybrid characteristics. They may be depicted as entertainment, talk shows, and news programs, sometimes they may feature debates and chit-chats that can be known as conversations talked to the viewer. What is seen as a presumptive viewer is studied according to how the very text is built up, and in which structure gaps both enables the fit of a concrete person and suggests reading paths of a presumptive audience who is nowhere except in the very textual materiality.